Potential and resilience: Evidence from peripheral regions of Germany - Valeria Maruseva; Henning Kroll (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2024)
Large and economically diverse countries often face a problem of regional imbalances which goes beyond a simple division between a core and a periphery. In large countries regions "out of the core" demonstrate substantial variety in economic, social and cultural terms, they have difference resource and technological base. These local specifics determine to large extent new their path development and ability to grasp the opportunities provided by ongoing socio-technological transformation. This paper suggests classification of non-core regions of Germany under relational perspective, taking into account not only geographical remoteness of these regions, but also their social, economic and demographic characteristics. Breaking down the periphery of Germany to several more homogeneous groups allows us to evaluate their resilience and potential in a more precise manner, providing thus a base for policy implications and future research.
Keywords: 330; regional development; non-core regions; regional classification; structural change; lock-in